Pemanfaatan Teknologi Informasi Untuk Meningkatkan Kinerja Karyawan Administrasi Universitas Muhammadiyah Surakarta - Dwiningsih, Retno, Ahmad Mardalis, SE.,MBA (2017)
The purpose of this study are 1) To determine the level of employee performance Administration Muhammadiyah University of Surakarta. 2) To examine the use of information technology at the University of Muhammadiyah Surakarta Administration. 3) To determine the effect of the use of information technology to employee performance Administration Muhammadiyah University of Surakarta. The sample in this study were 39 respondents. The sampling technique used in this research is purposive sampling method. Data analysis techniques used in the research is to test the validity, reliability test and multiple linear regression analysis. The results showed that 1) the employee's performance Administration Muhammadiyah University of Surakarta quite good. 2) All employees of the University of Muhammadiyah Surakarta Administration has been using information technology that has been provided. 3) Utilization of information technology has a significant positive effect on employee performance. Keywords: Utilization of Information Technology, User